Niosomal Drug Delivery - A Comprehensive Review - More, Vrunal V. (Asian Journal of Pharmaceutics (AJP), 2019)
Niosomes or non-ionic surfactant vesicles are microscopic lamellar structures formed on admixture of non-ionic surfactant of the alkyl or dialkyl polyglycerol ether class and cholesterol with subsequent hydration in aqueous media. They are vesicular systems similar to liposomes that can be used as carriers of amphiphilic and lipophilic drugs. The basic process of preparation is the same, i.e., hydration by aqueous phase of the lipid phase which may be either a pure surfactant or a mixture of surfactant with cholesterol. After preparing niosomal dispersion, unentrapped drug is separated by dialysis centrifugation or gel filtration. A method of in vitro release rate study includes the use of dialysis tubing. Niosomes are promising vehicle for drug delivery, and being non-ionic, it is less toxic and improves the therapeutic index of the drug by restricting its action to target cells. Niosomes are unilamellar or multilamellar vesicles formed from synthetic non-ionic surfactants. They are very similar to the liposomes. Niosomal drug delivery is potentially applicable to many pharmacological agents for their action against various diseases. Niosomes have numerous advantages so they are better option for drug delivery.